Quantifying post-transcriptional regulation in the development of Drosophila melanogaster - Kolja Becker (Nature Portfolio, 2018)
Proteome and transcriptome often show poor correlation, hindering the system-wide analysis of post-transcriptional regulation. Here, the authors study proteome and transcriptome dynamics during Drosophila embryogenesis and present basic mathematical models describing the temporal regulation of most protein-RNA pairs.